Three-band quantum well infrared photodetector using interband and intersubband transitions. - Fábio Durante Pereira Alves (2008)
This thesis presents the modeling, design, fabrication and characterization of a quantum well infrared photodetector (QWIP) capable of detecting near infrared (NIR), mid wavelength infrared (MWIR) and long wavelength infrared (LWIR), simultaneously. The NIR detection was achieved using interband transition while MWIR and LWIR were based on intersubband transition in the conduction band. The quantum-well structure was modeled by solving self-consistently the Schrödinger and Poisson equations with the help of the shooting method. A sample with three different stacks of quantum wells formed by different configurations of GaAs, AlGaAs and InGaAs, separated by n-doped GaAs contact layers was grown on a semi-insulated GaAs substrate using MBE (Molecular Beam Epitaxy). Intersubband absorption in the sample was measured for the MWIR and LWIR using Fourier transform spectroscopy (FTIR) and the measured peak positions were found at 5.3 and 8.7 ?m, respectively which are within 5% of the theoretical values, indicating the good accuracy of the self-consistent model. The test photodetectors were fabricated using a standard photolithography process with exposed middle contacts to allow separate bias and readout of signals from the three wavelength bands. A 45 degree facet was polished to allow light coupling. Performance analyses were conducted in order to obtain the I-V characteristics, responsivity and detectivity of each detection band. The background-limited infrared performance (BLIP) for the LWIR quantum wells shows an upper operating temperature of about 70 K, limiting the overall device. Photocurrent spectroscopy was performed and gave three peaks at 0.84, 5.0 and 8.5 m wavelengths with approximately 0.5, 0.03 and 0.13 A/W peak responsivities for NIR, MWIR and LWIR bands, respectively. Estimated peak detectivities, limited by the number of quantum well repetitions, are 140, 1.6 and 1.2x109 cm.Hz1/2/W for NIR, MWIR and LWIR, respectively. The overall results demonstrate the possibility of detection of widely separated wavelength bands, in a single pixel device, using interband and intersubband transitions in quantum wells.